Professional skills development for mathematics undergraduates. Issue 3 (21st December 2018) - Russell, Ewan; Rowlett, Peter
Abstract : Purpose: The purpose of this paper is to describe the design and development of a final year undergraduate mathematics module designed to address professional skills development at a UK university, including via input to curriculum and assessment from employers, and to investigate student acquisition of skills from this module. Design/methodology/approach: Literature on skills development in mathematics informs module design and development. Students optionally completed Likert-style competency questionnaires before and after the taught module content, and reflected on skills development via an end of module questionnaire. Data collection took place over three academic years. Findings: Several key competencies exhibit median increases over the course of the module in each academic year, indicating a perceived skills development. Problem solving and presentation skills are particularly highlighted. Research limitations/implications: Numbers of students were small, though the study is repeated with three different cohorts. Some students study mathematics jointly with another discipline and hence may have experience in skills development from the other subject. Practical implications: This study indicates that innovations in teaching style and assessment in mathematics modules can enhance student confidence and competence with key professional skills. Originality/value: Undergraduate modules in mathematics which have a focus on professional skills development are still fairly rare in UK universities. Often such modules do not embed the professional skills development activities with subject-specific technical tasks and projects as this module does. There are few formal studies of the effectiveness of this style of module, especially longitudinal studies covering several academic years.